PERAN BIDANG INVESTIGASI BPKP DKI JAKARTA DALAM PENCEGAHAN FRAUD DENGAN MENGGUNAKAN FRAUD CONTROL PLAN : THE ROLE OF THE DKI JAKARTA BPKP INVESTIGATION DIVISION IN FRAUD PREVENTION USING THE FRAUD CONTROL PLAN - Rimi Gusliana Mais; Ainun Komala Indah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to explore how the fraud control plan (FCP) used by the Financial and Development Supervisory Agency (BPKP) to detect fraud committed by BUMN. This study was used a qualitative approach using interviews with BPKP staff used to obtain comprehensive information in the field. The results of this studied indicate that the FCP has been actively was used by BPKP DKI Jakarta in recent years. Even though it can effectively detect fraud, several obstacles were found such as low knowledge, information technology technical skills, auditor independence and culture. Therefore, BPKP needs to carry out socialization and technical training efforts to increase partner awareness in preventing fraud that occurs in their respective institutions. FCP is an effective method for detecting fraud. But empirical evidence is still relatively rarely explored. This study offers new knowledge regarding internal audit and fraud prevention conducted by BPKP along with various practical implications for companies.